2020
DOI: 10.3390/particles3010004
|View full text |Cite
|
Sign up to set email alerts
|

Color Transparency and Hadron Formation Effects in High-Energy Reactions on Nuclei

Abstract: An incoming or outgoing hadron in a hard collision with large momentum transfer gets squeezed in the transverse direction to its momentum. In the case of nuclear targets, this leads to the reduced interaction of such hadrons with surrounding nucleons which is known as color transparency (CT). The identification of CT in exclusive processes on nuclear targets is of significant interest not only by itself but also due to the fact that CT is a necessary condition for the applicability of factorization for the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Pion p t spectrum is influenced by hadron formation only very weakly. In the collisions of heavier nuclei [338] the hadron formation effect becomes more pronounced, especially for central events.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Pion p t spectrum is influenced by hadron formation only very weakly. In the collisions of heavier nuclei [338] the hadron formation effect becomes more pronounced, especially for central events.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Even for Cornell and HERMES data with much higher Q 2 up to 10 GeV 2 , it was shown that the transverse cross section dominates [7]. The arguments from pQCD, thus, need to be taken with caution; indeed, in a recent publication [8], it is assumed that point-like configurations are formed both for longitudinal and transverse photons.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in a recent publication[7] the authors now assume that the point like configurations are formed both for longitudinal and transverse photons.…”
mentioning
confidence: 99%